Urine sodium dithionite test for determining prognosis and outcome of paraquat poisoning - Aimon Pradoo (2022)
Objective: To determine the association between urine sodium dithionite test result, testing time from paraquat (PQ) exposure, and mortality or systemic effect in patients with PQ poisoning. Materials and Methods: A retrospective study at the poison center identified cases with PQ exposure that receive urine sodium dithionite test results between 2015 and 2016. Urine sodium dithionite test results were reported in four groups, 1) no change in urine color, 2) green or light blue color, 3) dark blue color, and 4) purple or black color. Results: One hundred ten PQ exposures with urine sodium dithionite test results are included in the present analysis. Multivariate analysis showed that age, initial urine sodium dithionite test color, and testing time were independently associated with mortality. There were 26 deaths (23.6%). The mortality rate was different between groups classified by urine sodium dithionite test results and testing time from PQ exposure (p<0.01). In groups with the dithionite test performed within 12 hours of exposure, the mortality rates were 0 in the green or light blue group, 33.3% in the dark blue group, and 63.2% in the purple or black group. In groups with the dithionite test performed more than 12 hours after exposure, the mortality rates were 27.3% in the green or light blue group, 60.0% in the dark blue group, and 100% in the purple or black group. There were forty-eight patients with no change in urine color, all survived. In patients who survived, there were different systemic effect rates between groups classified by urine sodium dithionite test results and testing time. Conclusion: The initial urine sodium dithionite test result and testing time may be used as a tool to guide therapy and predict mortality and systemic involvement in patients with PQ poisoning.